Dissertations - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1998)
1. Inverse problems in fish target strength estimation [in Polish] by Marek Moszyński, Department of Acoustics, Technical University of Gdańsk, 18 November 1997; 2. The acoustic system for measurement of the nonlinearity parameter of the water medium using parabolic model [in Polish] by Krzysztof Zachariasz, Department of Acoustics, Technical University of Gdańsk, 16 December 1997, supervisor: A. Stepnowski; 3. Composite ultrasonic transducers for medical application [in Polish] by Krzysztof Kycia, Ultrasonic Department, Institute of Fundamental Technological Research, Polish Academy of Sciences, 22 January 1998, Zakład Ultradźwięków, supervisor: Andrzej Nowicki.